Tinjauan atas Prosedur Pemeriksaan Pendapatan Harian Food and Beverage pada Aston Bogor Hotel & Resort - Salsabil, Nafizhan; Amrulloh; Marlina, Tri (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Food and Beverage sales as one of the largest revenue generators in does not rule out the possibility of human error or fraud that can cause the revenue generated to be unknown or the authenticity of the revenue. So that the role of Income Audit is needed as a daily food and beverage income examiner. The purpose of writing this final project is to find out how the procedure for checking daily food and beverage income by Income Audit, to find out how the procedure for supervising the use of Restaurant Bill and Captain Order Slip, and to find out how Income Audit handles human error on minus posting by the food and beverage cashier section at Aston Bogor Hotel & Resort. The results of the review show that the procedure for checking daily food and beverage income by Income Audit at Aston Bogor Hotel & Resort has been running very well, because it is in accordance with the regulations set by the management. As well as the departments and sections related to the inspection of daily food and beverage income by Income Audit at Aston Hotel Bogor & Resort have also carried out their duties in accordance with the procedure. Keywords: Income Audit, daily income, Food and Beverage